SERVICE OPERATIONS MANAGEMENT FOR ENHANCING â€œHERITAGEâ€ EMOTIONS AT HOTEL SALAK, BOGOR - Hastjarjo Hastjarjo; Agus Prihanto; Nisa Rahmaniyah Utami (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2022)
We all know that a hotel must have a differentiation of service experience. But many hotels are historical buildings do not yet understand that they have a heritage competitive advantage, well. The